A Multi-center, Dose-escalation Study of Human type I Pancreatic Elastase (PRT-201) Administered after Arteriovenous Fistula Creation. Issue 2 (April 2013) - Peden, Eric K.; Leeser, David B.; Dixon, Bradley S.; El-Khatib, Mahmoud T.; Roy-Chaudhury, Prabir; Lawson, Jeffrey H.; Menard, Matthew T.; Dember, Laura M.; Glickman, Marc H.; Gustafson, Pamela N.; Blair, Andrew T.; Magill, Marianne; et al.
Purpose: To explore the safety and efficacy of PRT-201. Methods: Randomized, double-blind, placebo-controlled, single-dose escalation study of PRT-201 (0.0033 to 9 mg) applied after arteriovenous fistula (AVF) creation. Participants were followed for one year. The primary outcome measure was safety. Efficacy measures were the proportion with intra-operative increases in AVF outflow vein diameter or blood flow ≥25% (primary), changes in outflow vein diameter and blood flow, AVF maturation and lumen stenosis by ultrasound criteria and AVF patency. Results: The adverse events in the PRT-201 group (n=45) were similar to those in the placebo group (n=21). There were no differences in the proportion with ≥25% increase in vein diameter or blood flow, successful maturation or lumen stenosis. There was no statistically significant difference in primary patency between the dose groups (placebo n=21, Low Dose n=16, Medium Dose n=17 and High Dose n=12). In a subgroup analysis that excluded three participants with early surgical failures, the hazard ratio (HR) for primary patency loss of Low Dose compared with placebo was 0.38 (95% CI 0.10-1.41, P=0.15). In a Cox model, Low Dose (HR 0.27, 95% CI 0.04-0.79, P=0.09), white race (HR 0.17, 95% CI 0.03-0.79, P=0.02), and age <65 years (HR 0.25, CI 0.05-1.15, P=0.08) were associated (P<0.10) with a decreased risk of primary patency loss. Conclusions: PRT-201 was not different from placebo for safety or efficacy measures. There was a suggestion for improved AVF primary patency with Low Dose PRT-201 that is now being studied in a larger clinical trial.